2019
DOI: 10.1007/978-3-030-31784-3_10
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Algorithm for Computing Causal Trace Sets in Causality Checking

Abstract: Causality Checking [LL13a] has been proposed as a finite state space exploration technique which computes ordered sequences of events that are considered to cause the violation of a reachability property. A crucial point in the implementation of Causality Checking is the computation and storage of all minimal counterexamples found during state space exploration. We refer to the set of all minimal counterexamples as a causal trace set. However, the Duplicate State Prefix Matching (DSPM) Algorithm that is curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…There, causes for reachability properties are formulas of a temporal logic called event order logic, used to describe temporal relations between events. Algorithms to compute causes in this sense were also studied in [15,77], and the approach was extended to handle general LTL formulas as effects rather than just reachability in [20].…”
Section: Further Approaches Inspired By Hp Causalitymentioning
confidence: 99%
“…There, causes for reachability properties are formulas of a temporal logic called event order logic, used to describe temporal relations between events. Algorithms to compute causes in this sense were also studied in [15,77], and the approach was extended to handle general LTL formulas as effects rather than just reachability in [20].…”
Section: Further Approaches Inspired By Hp Causalitymentioning
confidence: 99%
“…Currently, QuantUM depicts the set of actions in a causality class by a fault tree without indicating the order of the contained actions. In previous work, amongst others we applied Causality Checking to the architecture of a self-driving car [KL19], and showed that Causality Checking supports the safety assessment in the development of a safety-critical system.…”
Section: Motivationmentioning
confidence: 99%
“…Afterwards, QuantUM pools the causal action traces with the same set of actions to a causality class. The disjunction of the different causality classes constitutes the cause of the property violation and will be displayed as a fault tree [KL19]. Currently, QuantUM depicts the set of actions in a causality class by a fault tree without indicating the order of the contained actions.…”
Section: Motivationmentioning
confidence: 99%
See 2 more Smart Citations